2006
DOI: 10.1186/1471-2377-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid receptor EP1 and Cox-2 in injured human nerves and a rat model of nerve injury: a time-course study

Abstract: BackgroundRecent studies show that inflammatory processes may contribute to neuropathic pain. Cyclooxygenase-2 (Cox-2) is an inducible enzyme responsible for production of prostanoids, which may sensitise sensory neurones via the EP1 receptor. We have recently reported that while macrophages infiltrate injured nerves within days of injury, they express increased Cox-2-immunoreactivity (Cox-2-IR) from 2 to 3 weeks after injury. We have now investigated the time course of EP1 and Cox-2 changes in injured human n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 60 publications
3
45
2
Order By: Relevance
“…A number of studies have demonstrated COX-2-IR in nerves (i.e., endoneurium) in response inflammatory stimuli alone or as a result of neural injury (13,31). In the present study, we have confirmed that COX-2-IR is present in nerve in the suburothelial plexus and that COX-2-IR nerve fibers increase in density in the trigone region of the urinary bladder with acute and chronic CYP-induced cystitis.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies have demonstrated COX-2-IR in nerves (i.e., endoneurium) in response inflammatory stimuli alone or as a result of neural injury (13,31). In the present study, we have confirmed that COX-2-IR is present in nerve in the suburothelial plexus and that COX-2-IR nerve fibers increase in density in the trigone region of the urinary bladder with acute and chronic CYP-induced cystitis.…”
Section: Discussionsupporting
confidence: 91%
“…COX-2 upregulation (peaking 4 -6 wk after injury) in the injured nerve was shown following CCI in the rat sciatic nerve or after surgical injury of human nerves (166). In these two models, an early EP 1 receptor upregulation (appearing from day 5 on) in the injured nerve fibers and the corresponding DRGs was revealed together with an early macrophage infiltration into the injured nerve that was followed by COX-2 upregulation only later (165). In the CCI model, EP 1 and EP 4 receptor upregulation was revealed in infiltrating macrophages and the Schwann cells of the injured sciatic nerve (778).…”
Section: H Role Of Endogenous Prostanoids In Peripheral Mechanisms Omentioning
confidence: 99%
“…These results suggest that spinal cyclooxygenase contributes to central sensitization during migraine. Current studies show that COX-2 is upregulated on microglia/macrophages in chronic pain models [51].…”
Section: Cyclooxygenase Inhibitors and The Treatment Of Allodynia In mentioning
confidence: 99%